Micronekton assemblages and bioregional setting of the Great Australian Bight: A temperate northern boundary current system. (November 2018) - Flynn, A.J.; Kloser, R.J.; Sutton, C.
Abstract: A multi-disciplinary pelagic ecosystem study of the Great Australian Bight (GAB) examined the micronekton communities and bioregionalisation in this area that harbours significant predator populations. Micronekton community structure and biomass differed between the eastern and central regions of the GAB. Regional differences were mainly driven by relatively high abundance of krill ( Nematoscelis megalops, Nyctiphanes australis and Euphausia similis ) in east GAB and high abundance of Maurolicus australis and chaetognaths in central GAB. Central GAB was also characterised by relatively high abundance of gelatinous zooplankton and small-bodied cephalopods. Lanternfishes were used as a model pelagic group to investigate the bioregional setting of the GAB. The analyses indicated that the oceanic habitats of the GAB had bioregional affinities with the subtropical Indian Ocean. However, over the continental slope, the east GAB had bioregional affinities with the Subtropical Convergence and grouped with western and southern Tasmania and the southern Tasman Sea. Lanternfish assemblage groups were compared against existing regionalisations that are based on physicochemical variables and the Delphi Method. No single existing scheme suitably reflected lanternfish assemblage distributions, but parsimonious boundaries from existing schema were identified. This study demonstrates that the central GAB, where oil-and-gas exploration occurs alongside Marine Protected Area management, needs to be considered as a separate bioregion to the east GAB for the purposes of identifying conservation values and monitoring requirements.